Designing One Nation The Politics of Economic Culture and Trade in Divided Germany, 1945-1990 - Schreiter, Katrin; Project Muse. (Oxford University Press, 2020)
"Designing One Nation explores how East and West Germans negotiated their country's postwar division at the juncture of economic and cultural politics. It is especially concerned with historical interconnections between the two Germanies in industrial design, economic structures, corporate ethos, trade, economic foreign policy and consumer culture, all of which are subsumed under the term "economic culture." It shows that post-war reconstruction, as envisioned and realized by a network of politicians, entrepreneurs, and cultural brokers, did more than to modernize the respective parts of Germany. Rather, through the national re-inscription of their material culture, here explored in the realm of interior design and furniture production, the two German states pursued an unprecedented effort to regain economic stability and political influence in post-war Europe's order. Significantly, what started as a Cold War competition for ideological superiority quickly turned into a shared, politically legitimizing quest for an untainted post-fascist modernity. Following products from the drawing board into the homes of ordinary Germans, this book thus offers unique insights into how converging visions of German industrial modernity created shared expectations about economic progress and living standards. The resulting economic culture linked the two Germanies together and acted internationally in a pan-German interest"--
Form Follows Function: Industrial Design and the Emergence of Postwar Economic Culture -- Producing Modern German Homes: The Economy of National Branding -- Intra-German Trade and the Aesthetic Dialectic of European Integration -- From Competition to Cooperation: Cold War Diplomacy of German Design -- Conservative Modernity: The Reception of Functionalism in German Living Rooms.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Functionalism in art -- History; Industrial design -- Social aspects -- Germany; German reunification question (1949-1990); Germany -- Economic conditions -- 1990-; Germany -- History -- 1945-1990.; Germany (East) -- Relations -- Germany (West); Germany (West) -- Relations -- Germany (East); Electronic books